2018
DOI: 10.1016/j.jpor.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia

Abstract: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 29 publications
3
39
1
Order By: Relevance
“…A controlled temperature at 37°C during the experiment is nevertheless important, because temperature was documented to affect DC of composite cements significantly, in particular when composite cements are solely allowed to self-cure [10]. According to the authors' knowledge, most papers measured initial DC at room temperature [11][12][13]. In this study, we maintained the environmental temperature at 37°C as in the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…A controlled temperature at 37°C during the experiment is nevertheless important, because temperature was documented to affect DC of composite cements significantly, in particular when composite cements are solely allowed to self-cure [10]. According to the authors' knowledge, most papers measured initial DC at room temperature [11][12][13]. In this study, we maintained the environmental temperature at 37°C as in the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Light curing is important for SADRC [12]. It affects the polymerization efficiency of dual-cured resin cement through high translucent zirconia [13]. In addition, curing time [14], type of light curing unit [15], type of initiator [16], the type [17], and thickness [18] of the restoration can influence the polymerization of dual-cured resin cement.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [10,25] found that bond strength is higher when the lightcuring time is prolonged from 20 s to 40 s. Thus, the light-curing time was set to 40 s, as suggested by previous studies [35,36]. Aluminum air abrasion and chemical pretreatment with an MDP-containing universal primer were performed for simulating the clinical routine procedure and follow previous reports [10,37,38].…”
Section: Discussionmentioning
confidence: 98%